2010
DOI: 10.1038/ejcn.2010.96
|View full text |Cite
|
Sign up to set email alerts
|

The glycaemic potency of breakfast and cognitive function in school children

Abstract: Objectives: The aim of this study was to assess how the glycaemic potency (blood glucose (BG)-raising potential) of breakfast is associated with cognitive function (CF) in school children, taking into account important confounders, including iron status, underlying physiological adaptations and socio-economic status. Methods: Sixty children aged 11-14 years were selected on the basis of having breakfast habitually. Their breakfast and any snacks eaten on the morning of the study were recorded. They were catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
57
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 48 publications
3
57
0
2
Order By: Relevance
“…This study presented a contrast of extremes of GI and GL after a matched high carbohydrate load. Hence, the efficacy of lowering GL on cognitive performance may only be relevant if the carbohydrate load is maintained, which is in line with the suggestions of Micha et al 19,21 Despite different glycaemic responses between the three breakfasts, we observed no effects in appetite or cognition over the 3-h testing period. A low-GL meal, which is also low in carbohydrate, sustained glucose levels above baseline for just beyond 1 h in our children.…”
Section: Discussionsupporting
confidence: 77%
“…This study presented a contrast of extremes of GI and GL after a matched high carbohydrate load. Hence, the efficacy of lowering GL on cognitive performance may only be relevant if the carbohydrate load is maintained, which is in line with the suggestions of Micha et al 19,21 Despite different glycaemic responses between the three breakfasts, we observed no effects in appetite or cognition over the 3-h testing period. A low-GL meal, which is also low in carbohydrate, sustained glucose levels above baseline for just beyond 1 h in our children.…”
Section: Discussionsupporting
confidence: 77%
“…Greater attention in class and engagement in learning activities are likely to be associated with productive learning outcomes and better academic achievement. The mechanism for the observed effect on learning behaviour may be related to the physiological effects of improving nutritional status as observed in previous research on attention, memory and cognitive performance (Wesnes et al, 2003;Ingwersen et al, 2007;Benton and Stevens, 2008;Micha et al, 2010), but the effect may also be attributable to a combination of mechanisms. Changes to the dining environment, which improve service flow or enhance the eating environment, also facilitate both physical and social activities.…”
Section: Discussionmentioning
confidence: 91%
“…Published intervention studies have mainly investigated the effect of nutrient supplements and the presence/absence and content of the breakfast meal on a range of subjective and objective learning outcomes (Dickie and Bender, 1982;Meyers et al, 1989;Southon et al, 1994;Wolraich et al, 1994;Rampersaud et al, 2005;Dalton et al, 2009;Micha et al, 2010). Few studies have addressed the relationship between school lunch consumption and educational outcomes (Gietzen and Vermeersch, 1980;Kim et al, 2003;Florence et al, 2008;Selvik Ask et al, 2010) and no study has focussed on classroom behaviour in the post-lunchtime period.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that insulin resistance appears to be a peripheral postprandial phenomenon, 17,19,24,29,30 it can be speculated that the improvement seen in the cognitive tests after the G-WWB may be a consequence of an acutely improved insulin sensitivity within the brain. In an animal model, there was a failure in insulin resistant and obese rats to enhance plasma membrane GLUT4 translocation in hippocampus, despite elevation in plasma glucose; and no changes were found in the density of insulin receptors and in total GLUT4.…”
mentioning
confidence: 99%